Quantum phase transitions in highly crystalline two-dimensional superconductors - Yu Saito (Nature Portfolio, 2018)
Superconductor-insulator transitions predominantly occur in highly disordered thin films. Here, Saito et al. report that a quantum metallic state transforms via the quantum Griffiths state to a weakly localized metal at high magnetic fields in a crystalline two-dimensional superconductor.